2023
DOI: 10.5194/bg-20-3481-2023
|View full text |Cite
|
Sign up to set email alerts
|

Experiments of the efficacy of tree ring blue intensity as a climate proxy in central and western China

Yonghong Zheng,
Huanfeng Shen,
Rory Abernethy
et al.

Abstract: Abstract. To investigate the potential value of tree ring blue intensity as a robust climate proxy in central and western China, four species from five sites were assessed. As well as latewood inverted blue intensity, we also examined earlywood blue intensity. To explore the sensitivity of using different extraction parameter settings using the software CooRecorder, seven percentile (P) variant settings for earlywood blue intensity and latewood inverted blue intensity were used, namely P50 : 50, P60 : 40, P70 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In particular, the MANE region is underrepresented due to a lack of temperaturesensitive tree-ring records. Since the creation of the N-TREND network, advances in dendrochronological techniques such as blue intensity (McCarroll et al, 2002) have demonstrated the ability to provide robust paleotemperature estimates at the mid-to-lower latitudes across many regions of the Northern Hemisphere (Heeter et al, 2019(Heeter et al, , 2020(Heeter et al, , 2021Cao et al, 2022;Zheng et al, 2023). In North America, recent work (Wang et al, 2022;Harley et al, 2021)…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the MANE region is underrepresented due to a lack of temperaturesensitive tree-ring records. Since the creation of the N-TREND network, advances in dendrochronological techniques such as blue intensity (McCarroll et al, 2002) have demonstrated the ability to provide robust paleotemperature estimates at the mid-to-lower latitudes across many regions of the Northern Hemisphere (Heeter et al, 2019(Heeter et al, , 2020(Heeter et al, , 2021Cao et al, 2022;Zheng et al, 2023). In North America, recent work (Wang et al, 2022;Harley et al, 2021)…”
Section: Introductionmentioning
confidence: 99%